PELATIHAN MANAJEMEN KAS DALAM PENYUSUNAN ANGGARAN PADA SEKOLAH AL WASLIYAH 2 PERDAGANGAN - Zulia Almaida Siregar (Jurnal Abdi Mas Adzkia, 2022)
Cash management is usually carried out in companies in the financial planning process which is routine and relatively small in number. Cash Management is used to mark relatively small management expenses such as purchasing office stationery, consumption funds for meeting purposes. As a person who is trusted by the leadership to manage cash, he must be able to organize and plan petty cash funds and make financial records that are re-booked by the company's finance department using the imprest and fluctuation methods. Many students still do not understand how and techniques to create and plan cash, therefore this cash management training is very important for students of SMK Al-Wasliyah Trading, Simalungun Regency in order to face the Expertise Competency Test (UKK) and the National Examination (UKK). UN) so that students can work on exam questions quickly and accurately. After participating in this training, it is hoped that the students of SMK Al-Wasliyah Trading, Simalungun Regency can gain insight and knowledge about the methods and techniques for preparing cash management in solving exam questions quickly and precisely in accordance with the allotted time and the graduation rate reaches 100 %